Orthodontic Treatment Knowledge among General Dentists and Non-orthodontic Specialists - Acharya, Asal; Mishra, Praveen; Shrestha, Rabindra Man; Shah, Pooja (Orthodontic Journal of Nepal, 2019)
Introduction: General dentists and specialists other than orthodontist may encounter patient requiring orthodontic treatment. For proper counseling and referral, it is important that general dentists and non-orthodontic specialists have adequate level of orthodontic knowledge. Objective: To assess the knowledge of orthodontic treatment among general dentists and non-orthodontic specialists and to compare the knowledge between the two groups. Materials & Method: A descriptive cross sectional study using questionnaire was performed among 185 actively practicing general dentists and non-orthodontic specialists of Nepal. The questionnaire comprised of three parts. The first part included demographic details, second part contained 5 multiple choice questions regarding orthodontic counseling and third part integrated 18 questions for evaluating knowledge of orthodontic treatment. Each correct answer was given score 1 and every incorrect answer was scored zero in the third part of the questionnaire. Result: Among total participants, 60.5% think first orthodontic evaluation of a child should be carried out within 7 to 8 years of age and 44.3% think orthodontic treatment can even be started after 40 years of age. Around 66% of the participants think that orthodontic treatment cannot be performed in periodontally compromised cases. No significant difference was found between the mean scores of knowledge among general dentists and non-orthodontic specialists (p=0.891), or among dentists with different years of experience (p=0.644). Conclusion: There is a need for more education of orthodontic treatment concepts to the dentists who do not belong to orthodontic field for proper counseling and referral.